Auditoría interna y el proceso contable en el Instituto de Investigaciones de la Amazonía Peruana Iquitos 2023 - Saberbein Caballero, Roberto Ronnel (2024)
The objective of this report was to relate the internal audit with the accounting process at the Peruvian Amazon Research Institute, Iquitos 2023, where an applied methodology, descriptive and correlational level with a non experimental design was used. 93 servers were taken as a sample and a questionnaire was used to collect information. According to the results obtained, the internal audit at the Peruvian Amazon Research Institute, Iquitos, is regular due to the lack of clarity in the identification of evaluation needs. Although control mechanisms are adequate, recommendations are sometimes made to address and improve deficiencies found. Regarding the accounting process, it is carried out on a regular basis, sometimes the system interface provides validations and controls to ensure the consistency and accuracy of the data entered, but mostly digital accounting books are used to record financial operations. Likewise, various methods are used to analyze the company's financial statements. However, the resulting financial reports are often not presented in a clear and organized manner. Finally, it is concluded that there is a strong positive correlation between the internal audit and the accounting process, demonstrated by a coefficient of 0.767 and a significance of 0.000.